Syntheses, crystal structures and optical properties of two one‐dimensional germanophosphates: HRb3Ge2(HPO4)6 and CsGe(HPO4)2(OH). Issue 10 (26th September 2018) - Song, Jun-Ling; Lu, Wen-Xiu; Guo, Tian-Shuo; Zhou, Yu-Hua
Abstract : Two one‐dimensional alkali‐metal germanophosphates (GePOs), namely, HRb3 Ge2 (HPO4 )6 and CsGe(HPO4 )2 (OH), have been prepared by the solvothermal method. The former shows one‐dimensional (1D) [Ge(HPO4 )6 ]∞ chains along the c axis and the latter shows 1D [Ge(HPO4 )4 (OH)2 ]∞ chains. Abstract : Germanophosphates, as a young class of metal phosphates, have been less reported but might possess more diverse structural types and potential applications. Here, two one‐dimensional (1D) alkali‐metal germanophosphates (GePOs), namely, hydrogen hexakis(μ‐hydrogen phosphato)digermaniumtrirubidium, HRb3 Ge2 (HPO4 )6 (1 ), and caesium bis(μ‐hydrogen phosphato)(μ‐hydroxido)germanium, CsGe(HPO4 )2 (OH) (2 ), have been prepared by the solvothermal method. Compound1 shows 1D [Ge(HPO4 )6 ]∞ chains along the c axis formed by GeO6 octahedra and PO4 tetrahedra, with Rb + cations dissociated between the chains. Compound2 also exhibits 1D [Ge(HPO4 )4 (OH)2 ]∞ chains constructed from adjacent Ge(HPO4 )4 (OH)2 octahedra, with Cs + cations dissociated between the chains. XRD, TGA, IR and UV–Vis–NIR absorption spectra are presented and discussed for both compounds.